Continuous treatment of the insensitive munitions compound N-methyl-p-nitro aniline (MNA) in an upflow anaerobic sludge blanket (UASB) bioreactor. (February 2016) - Olivares, Christopher I.; Wang, Junqin; Silva Luna, Carlos D.; Field, Jim A.; Abrell, Leif; Sierra-Alvarez, Reyes
Abstract: N-methyl- p -nitroaniline (MNA) is an ingredient of insensitive munitions (IM) compounds that serves as a plasticizer and helps reduce unwanted detonations. As its use becomes widespread, MNA waste streams will be generated, necessitating viable treatment options. We studied MNA biodegradation and its inhibition potential to a representative anaerobic microbial population in wastewater treatment, methanogens. Anaerobic biodegradation and toxicity assays were performed and an up-flow anaerobic sludge blanket reactor (UASB) was operated to test continuous degradation of MNA. MNA was transformed almost stoichiometrically to N-methyl- p -phenylenediamine (MPD). MPD was not mineralized; however, it was readily autoxidized and polymerized extensively upon aeration at pH = 9. In the UASB reactor, MNA was fully degraded up to a loading rate of 297.5 μM MNA d −1 . Regarding toxicity, MNA was very inhibitory to acetoclastic methanogens (IC50 = 103 μM) whereas MPD was much less toxic, causing only 13.9% inhibition at the highest concentration tested (1025 μM). The results taken as a whole indicate that anaerobic sludge can transform MNA to MPD continuously, and that the transformation decreases the cytotoxicity of the parent pollutant. MPD can be removed through extensive polymerization. These insights could help define efficient treatment options for waste streams polluted with MNA. Highlights: N-methyl-p-nitroaniline (MNA) is microbially reduced to p-phenylenediamine (MPD). MPD is unstable and undergoes polymerization when exposed to air at pH ≥ 7. MNA is a strong methanogenic inhibitor (IC50 = 103 μM), but MPD was not toxic.